Kualitas Pelayanan Publik Pada Kantor Agraria Tata Ruang Badan Pertanahan Nasional (Atr Bpn) Kabupaten Landak Provinsi Kalimantan Barat - Pardiyansyah S.; Ida Rachmawati; Meita Istianda (Jurnal Pendidikan Indonesia, 2025)
This study aims to evaluate the quality of public services at the Agrarian and Spatial Planning Office of the National Land Agency (ATR BPN) in Landak Regency, West Kalimantan Province. The study employs a qualitative approach using observation and in-depth interviews with employees and service users. The analysis is based on the five service quality dimensions proposed by Parasuraman, Zeithaml, and Berry: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The findings indicate that the ATR BPN Landak office provides adequate physical facilities and basic services, such as comfortable waiting rooms, parking areas, children’s play areas, lactation rooms, and digital queue systems. However, significant challenges remain, including limited staff, absence of electronic payment (EDC) systems, unstable internet infrastructure, and limited digital literacy and socialization. These issues result in frequent delays in processing new land certificate applications, difficulty accessing information, and inconsistent service reliability. The study concludes that improving human resource capacity, technological infrastructure, and information communication are critical steps to enhance public service quality at ATR BPN Landak.